A class of Covariate-Adjusted Response-Adaptive Allocation Designs for Multitreatment Binary Response Trials. Issue 5 (3rd September 2018) - Biswas, Atanu; Bhattacharya, Rahul
ABSTRACT: A class of covariate-adjusted response-adaptive randomization procedures is developed for binary treatment outcomes in a phase III clinical trial set up involving multiple treatments. The target allocation is developed by combining the ethical aspects with statistical precision under the existence of treatment covariate interaction. Relevant measures of the performance for the proposed allocation designs are studied and compared.